2016
DOI: 10.1371/journal.pone.0153729
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Mesenchymal Stem Cells Attenuate Mitochondria Damage Induced by Hypoxia in Mouse Trophoblasts

Abstract: ObjectiveWe aimed to observe the change of mitochondrial function and structure as well as the cell function induced by hypoxia in mouse trophoblasts, and moreover, to validate the restoration of these changes after co-culture with bone marrow mesenchymal stem cells (hereinafter referred to as “MSCs”). Further, we explored the mechanism of MSCs attenuating the functional damage of trophoblasts caused by hypoxia.MethodsCells were divided into two groups, trophoblasts and MSCs+trophoblasts respectively, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In this case, MSCs can significantly improve the symptoms of Th1 cells of PE mouse model, implying that MSCs may play a significant role in maternal interface immunity [ 158 ]. Consistent with these, another study demonstrated that MSCs could improve the functions of mouse trophoblasts and endothelial cells to promote angiogenesis through attenuating the hypoxia-induced mitochondria damage [ 159 ]. As for the underlying mechanisms, there is increasing evidence that the beneficial effects of MSCs are exerted through the secretory bodies and reducing SFLT-1 to restore angiogenesis.…”
Section: Novel Pe Treatmentsmentioning
confidence: 70%
“…In this case, MSCs can significantly improve the symptoms of Th1 cells of PE mouse model, implying that MSCs may play a significant role in maternal interface immunity [ 158 ]. Consistent with these, another study demonstrated that MSCs could improve the functions of mouse trophoblasts and endothelial cells to promote angiogenesis through attenuating the hypoxia-induced mitochondria damage [ 159 ]. As for the underlying mechanisms, there is increasing evidence that the beneficial effects of MSCs are exerted through the secretory bodies and reducing SFLT-1 to restore angiogenesis.…”
Section: Novel Pe Treatmentsmentioning
confidence: 70%
“…Apoptosis is frequently accompanied by abnormal mitochondrial morphology and function (Lv et al, 2021; Wang et al, 2022). It has been found that hypoxia triggers mitochondrial damage in mouse trophoblast cells (Wang et al, 2016). Inhibition of the mitochondrial apoptotic pathway attenuates hypoxia‐induced trophoblast cell damage (Ma et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia brings on disarrangement of mitochondrial ultrastructure in mice trophoblasts in vitro. bm-MSCs intensify mitochondrial membrane potential and increase ATP production/consumption in trophoblast and support cell survival against hypoxia (100). PD−MSCs reduce 10.3389/fmed.2022.923334 mitochondrial damage by downregulating Heat shock protein 60 (HSP60) (inducted under mitochondrial stress) and upregulating prohibitin 1 (PHB1) (involved in stabilizing mitochondria) expression and promoting ATP generation/consumption by upregulating VDAC in the mitochondria of trophoblast cells (101).…”
Section: Mesenchymal Stem Cells Regulate Mitochondrial Metabolismmentioning
confidence: 99%